Prospect of energy conservation measures (ECMs) in buildings subject to climate change : A systematic review - Duan, Zhuocheng; de Wilde, Pieter ; 0000-0003-3376-9775; Attia, Shady; Zuo, Jian (Energy and Buildings, 2024)
Energy conservation measures (ECMs) are often chosen for their immediate benefits, such as suitability to past/current climate conditions and rapid economic returns. However, the longevity of these ECMs poses a risk of becoming outdated or ineffective as climate change alters the very climatic parameters they were designed for. This paper provides insight into the foresight required when selecting an ECM, focusing on its long-term viability under global warming. The ECMs discussed encompass passive strategies such as building envelope insulation and window design, active systems like efficient HVAC and heat pumps, and renewable systems. The need for context-specific ECM selection tailored to local climate, building type, and cost-effectiveness is highlighted. Major challenges and barriers influencing the widespread adoption of ECMs under global warming are addressed, including: 1) considering long-term effectiveness in ECM decision-making, as measures effective initially may become disadvantageous in the future, and vice versa; 2) adopting a life cycle perspective considering both embodied and operational impacts; 3) developing robust, resilient building designs under climate change uncertainty; and 4) potential strategy shifts, such as transitioning from passive cooling techniques to active cooling systems. Meanwhile, policy interventions through regular updates to building codes and standards are needed to keep pace with evolving climate conditions and engage diverse stakeholders to balance multiple objectives, including environmental, societal, and human factors. Incorporating climate change into decision-making for ECM implementation is paramount for building energy adaptation to a warming climate.
Keywords: Adaptation and mitigation; Decisions with long time horizons; Energy consumption; Energy saving; Global warming; Heating and cooling energy; Trade-off